If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + x + 2(2) + 39 = 180 Multiply 2 * 2 2x + x + 4 + 39 = 180 Reorder the terms: 4 + 39 + 2x + x = 180 Combine like terms: 4 + 39 = 43 43 + 2x + x = 180 Combine like terms: 2x + x = 3x 43 + 3x = 180 Solving 43 + 3x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-43' to each side of the equation. 43 + -43 + 3x = 180 + -43 Combine like terms: 43 + -43 = 0 0 + 3x = 180 + -43 3x = 180 + -43 Combine like terms: 180 + -43 = 137 3x = 137 Divide each side by '3'. x = 45.66666667 Simplifying x = 45.66666667
| 4ab+a= | | 7p+2=5p+9 | | -7=-2+U | | 7x-110=64+x | | 62+2+3x=62 | | 2236000+-17740x=-71.2514 | | 4/5x+2/5=4/5 | | (9-4)*3=12 | | f(x)=2(0.75) | | 3x-20=7x-4 | | 2x+x+2(2)+89=180 | | 15r^2=-7r+4 | | 7x-37=29+4x | | 30+8y=-7y | | (14x-22)(x+11)=240 | | 4y-12=14 | | 2y-7x=-10 | | 3x+2[x+7]-5=4[x+3]-3[x+1] | | 20x-15=-8 | | 8w^2-18+9= | | 6H+H-20=44-H | | 2[4+2(5-x)-2x]=4(7-2x) | | 6H+H-20=44 | | 2z^2=5z-2 | | 2x+9x+12=6 | | 2x^2-4y=8 | | y-7=3(x-6) | | 8x-28=16+6x | | 70x+25(80)=60x+60(80) | | 4(1+X)=2(2+X) | | 14=50x | | x+7=-61 |